2019
DOI: 10.1186/s12864-019-5830-y
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptome analysis reveals differential immune related genes expression in bovine viral diarrhea virus-2 infected goat peripheral blood mononuclear cells (PBMCs)

Abstract: Background Bovine viral diarrhea virus (BVDV) is an economically important viral pathogen of domestic and wild ruminants. Apart from cattle, small ruminants (goats and sheep) are also the susceptible hosts for BVDV. BVDV infection could interfere both of the innate and adaptive immunity of the host, while the genes and mechanisms responsible for these effects have not yet been fully understood. Peripheral blood mononuclear cells (PBMCs) play a pivotal role in the immune responses to viral infectio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

5
40
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(45 citation statements)
references
References 60 publications
5
40
0
Order By: Relevance
“…Bovine viral diarrhea virus (BVDV) is an economically important pathogen of domestic and wild ruminants affecting multiple organ systems, incurring most economic losses due to respiratory diseases, low reproductive performance (due to reduced conception rates), early embryonic deaths, abortion, congenital weak calves, and high costs of control programs [1][2][3][4]. BVDV belongs to the genus Pestivirus within the family Flaviviridae, with two species, namely BVDV1 and BVDV2; both consist of strains, belonging to biotypes non-cytopathogenic or cytopathogenic, based on cell-cultured characteristics [5].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Bovine viral diarrhea virus (BVDV) is an economically important pathogen of domestic and wild ruminants affecting multiple organ systems, incurring most economic losses due to respiratory diseases, low reproductive performance (due to reduced conception rates), early embryonic deaths, abortion, congenital weak calves, and high costs of control programs [1][2][3][4]. BVDV belongs to the genus Pestivirus within the family Flaviviridae, with two species, namely BVDV1 and BVDV2; both consist of strains, belonging to biotypes non-cytopathogenic or cytopathogenic, based on cell-cultured characteristics [5].…”
Section: Introductionmentioning
confidence: 99%
“…In addition, recent studies reported that the immunosuppressive ability of BVDV heightens other viral disease potentiators, particularly the bovine respiratory disease [8][9][10]. The differences in genotypes and biotypes of BVDV, a wide range of susceptible hosts, the ability to induce persistent infection, and intervene with both innate and adaptive immunity, makes the prevention and control program difficult [4].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…As shown in many studies, high-throughput RNA-Sequencing (RNA-Seq) technology is an excellent approach to study the transcriptional levels of large numbers of genes in tissues or organisms. The results of sequencing data can provide the "whole picture" of the gene expression profile in the organisms [18][19][20][21]. Obtained genes were annotated upon Protein family (Pfam), Superfamily, Gene Ontology (GO) and Kyoto Encyclopedia of Genes and Genomes (KEGG) database for characterizing their functions at the molecular and cellular levels [22][23][24][25].…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, Venn diagram analysis was used to study the special expression of genes in each group, and then performed GO and KEGG enrichment to analyze functional categories [5,22]. Therefore, the database of Search Tool for the Retrieval of Interacting Genes (STRING) was used to study functional interaction of proteins (including stable complexes, metabolic pathways and a bewildering array of direct and indirect regulatory interactions), which was also usually used to analyze the transcriptomic profile [19,26]. Therefore, our study employed transcriptome sequencing to investigate the alteration of physiological metabolism and immune in the aestivation stage, and then analyze the potential associations between them.…”
Section: Introductionmentioning
confidence: 99%